The role of dissolved rice husk ash in the development of binary blast furnace slag-sewage sludge ash alkali-activated mortars - Istuque, Danilo Bordan [UNESP]; Payá, Jordi; Soriano, Lourdes; Borrachero, Maria Victoria; Monzó, José; Tashima, Mauro Mitsuuchi [UNESP] (Elsevier, 2022)
This study evaluated the compressive strength performance and microstructure of binary blast furnace slag-sewage sludge ash (BFS-SSA) alkali-activated mortars, in which rice husk ash (RHA) was dissolved in NaOH solution to replace commercial sodium silicate. The dissolution of RHA, performed in a thermal bottle with NaOH solution, enhanced the compressive strength of the alkali-activated mortars based on BFS up to 4.5-fold. BFS-SSA based mortars (10–40% SSA), activated with NaOH/RHA-based sodium silicate suspensions, reached a compressive strength up to 30 MPa after 28 curing days at 20°C. The RHA dissolution enhanced the strength and sustainability of the BFS-SSA alkali-activated mortars.
Keywords: Alkaline activation; Blast furnace slag; Microstructure; Rice husk ash; Sewage sludge ash; Sodium silicate suspensions